LSD1 Demethylates and Destabilizes Autophagy Protein LC3B in Ovarian Cancer - Mingyang Li; Jie Feng; Kangrong Zhao; Ting Huang; Bowen Zhang; Yifan Yang; Aiqin Sun; Qiong Lin; Genbao Shao (Biomolecules)
Autophagy is a complex cellular process that can either promote or inhibit cancer progression and development, depending on the context and molecular regulation involved. This study investigates how LSD1 regulates autophagy in ovarian cancer by interacting with the autophagy protein LC3B. Utilizing the bioinformatic analysis of TCGA, CPTAC, and GEO datasets, as well as immunohistochemistry in ovarian cancer patients, we explored the expression association between LSD1 and LC3B. Molecular mechanisms were further analyzed using Western blotting, immunoprecipitation, and GST pull-down assays. Our findings reveal that LSD1 binds to LC3B via its SWIRM domain, and high levels of LSD1 are closely associated with aggressive ovarian cancer and poor patient outcomes. Mechanistically, LSD1 demethylates LC3B, leading to decreased LC3B stability. The observed inverse correlation between LSD1 expression and LC3B protein levels in clinical samples underscores the need for further investigation to elucidate how reduced LC3B protein levels induced by LSD1 demethylation may contribute to ovarian cancer.